UPAYA MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN PADA ANAK USIA DINI 4-5 TAHUN MELALUI ALAT PERMAINAN EDUKATIF PUZZLE BUAH ANGKA DI TK HARAPAN INDONESIA II BEKASI - Astuti, Dwi Ridi; Darmiyanti, Astuti (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
Through the use of educational play media in the form of number puzzles, the aim of this research is to improve the ability of children aged 4 to 5 years at TK Harapan Indonesia II Bekasi in recognizing number symbols. The ability to recognize number symbols is a fundamental skill that is crucial for cognitive development in early childhood. As one of the educational play tools, the fruit number puzzle is expected to be an effective medium for teaching children about number shapes in a fun and interactive way. The research employed the Classroom Action Research (CAR) method, conducted in two cycles. The study involved 10 children aged 4 to 5 years from TK Harapan Indonesia II Bekasi, with each cycle consisting of planning, implementation, observation, and ending with reflection. Data were collected through direct observation during learning activities, pre- and post-tests to measure the ability to recognize number symbols, and teacher interviews to gather feedback on the learning process. The research results showed a significant improvement in the children's ability to recognize number symbols after the use of the fruit number puzzle. In the pre-test, the average recognition ability was 46%, while after the implementation of the fruit number puzzle, the average increased to 86%. The increased attendance and active participation of the children during the learning process demonstrated a rise in their interest and motivation in learning basic mathematics through the use of the fruit number puzzle in activities focused on recognizing number symbols. Based on the results of the research, it can be concluded that the use of the fruit number puzzle as an educational play medium is highly effective in enhancing the understanding of number symbols in children aged 4 to 5 years. The number puzzle not only helps introduce number symbols but also improves fine motor skills and cognitive abilities. This research provides an important contribution to early childhood education approaches.